The Influence of Creative Dance Learning Through the Tik Tok Application Media on the Physical Development of Gross Motor Children Aged 5-6 Years - Mutiya, Ana Septiyani; Dewanti H, Sri Sularti (BELIA: Early Childhood Education Papers, 2024)
The growth and development of early childhood is hampered during the COVID-19 pandemic. Even though children are at the age of golden age, where the process of growth and development is very rapid. One of the important developments to be developed is gross motor development. With the child's condition still being limited due to the epidemic that occurred, the researchers had the idea to develop children's gross motor skills with creative dance through the tik tok application media which was in great demand. The tik tok application media was chosen because of increasingly sophisticated technology and of course children follow the trends and developments of the times at this time. Methods This research is a field research with the type of experimental research. Sampling using purposive sampling technique, namely the selection of subjects is done in accordance with the characteristics or characteristics of the population and research objectives. Subjects aged 5-6 years as many as 31 children. Methods of data collection using interview techniques, observation and documentation. The hypothesis proposed in this study is whether creative dance learning through the tiktok application media affects the gross motoric physical development of children aged 5-6 years in Banjurpasar Village. With the results H0 is rejected and Ha is accepted with a Sig value of 0.000 less than 0.05. In this study, the questionnaire used has a correlation value above 0.3, which means that this questionnaire is truly valid, and has a reliable value of 0.775, which means that the test used by the researcher is quite reliable to use.